Centring 'being undetectable' as the new face of HIV: Transforming subjectivities via the discursive practices of HIV treatment as prevention. Issue 2 (June 2018) - Lloyd, Karen
Abstract HIV treatment as prevention is an emerging biomedical prevention approach utilising routine HIV testing, immediate engagement in HIV care, and the consumption of antiretrovirals to suppress individuals' viral loads, greatly reducing or eliminating the risk of onward transmission of HIV. Drawing on interviews with HIV scientists, policymakers, clinicians, and advocates, ethnographic field work at three global HIV scientific meetings, and analysis of textual and visual discourse data, I argue that several meso-level discursive practices are transforming the conditions of possibility for living with HIV. I explore three empirical sites—The Elite Society of the Undetectables, Housing Works' The Undetectables Project, and AIDS Vancouver's 'reimagining' of the Red Ribbon—where 'being undetectable', that is, having an HIV viral load that is so low as to be non-infectious, is coming to be centred as the best, perhapsonly, way to live as a person with HIV. The centring of 'being undetectable' as a technoscientific identity has critical implications for transformations in subjectivity, for the configuring of the moral borders between those who achieve viral suppression and those who do not, and also for the future it becomes possible to anticipate, including the achievement of the so-called 'End of AIDS'.